Reduced Activity of Sphingosine-1-Phosphate Lyase Induces Podocyte-related Glomerular Proteinuria, Skin Irritation, and Platelet Activation. (July 2015) - Schümann, Jens; Grevot, Armelle; Ledieu, David; Wolf, Armin; Schubart, Anna; Piaia, Alessandro; Sutter, Esther; Côté, Serge; Beerli, Christian; Pognan, François; Billich, Andreas; Moulin, Pierre; et al.
Sphingosine-1-phosphate (S1P) lyase is considered as a drug target in autoimmune diseases based on the protective effect of reducing activity of the enzyme in animal models of inflammation. Since S1P lyase deficiency in mice causes a severe, lethal phenotype, it was of interest to investigate any pathological alterations associated with only partially reduced activity of S1P lyase as may be encountered upon pharmacological inhibition. Both genetic reduction of S1P lyase activity in mice and inhibition of S1P lyase with a low-molecular-weight compound in rats consistently resulted in podocyte-based kidney toxicity, which is the most severe finding. In addition, skin irritation and platelet activation were observed in both instances. The similarity of the findings in both the genetic model and the pharmacological study supports the value of analyzing inducible partially target-deficient mice for safety assessment. If the findings described in rodents translate to humans, target-related toxicity, particularly podocyte dysfunction, may limit chronic systemic treatment of autoimmune diseases with S1P lyase inhibitors. Furthermore, partial deficiency or inhibition of S1P lyase appears to provide an in vivo rodent model to enable studies on the mechanism of podocyte dysfunction.